FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEMANDIRIAN PADA LANJUT USIA DALAM PEMENUHAN ACTIVITIY OF DAILY LIVING - Wijaya, Leni; Rikardo, Rendi (LPPM STIKes Mitra Adiguna, 2024)
Based on data from the World Health Organization (WHO) 2020, it is known that the population aged > 60 years (elderly) in 2020 is 22%. Actually, the decline that occurs in the elderly will reduce muscle mass and flexibility, so it can affect the capacity of the elderly to fulfill their activities. Factors that affect the level of independence of the elderly in carrying out daily activities such as age, immobility and easy falls. The purpose of this study was to determine the factors related to the level of independence in the elderly in fulfilling the Activity of Daily Living (ADL) at Harapan Kita Social Institution Palembang . Methods: The research design used in this study was an analytic survey with a cross sectional approach. The population in this study were all officers at the Harapan Kita Pale Social Institution for the Elderly. The population in this study were all the elderly living at the Harapan Kita Palembang Social Institution for the Elderly. The total population in this study was 53 people, the sampling technique used total sampling with a sample of 53 respondents. Data collection using a questionnaire. Data analysis used univariate and bivariate analysis with the chi square test. Results: there is a relationship between age (p value = 0.019), immobility (p value = 0.006), easy to fall (p value = 0.026) and the level of independence of the elderly in fulfilling ADLs at the Harapan Kita Social Home for the Elderly in Palembang. Suggestion: it is hoped that this can be a consideration for health workers, especially nurses in caring for the elderly to meet ADL needs. Service improvements can have a fairly good impact on the quality of the elderly and an increase in the welfare of the elderly can be achieved.